PEMANFAATAN TUMBUHAN OBAT DI DESA RUMOONG, RUMOONG ATAS II, TUMALUNTUNG, TUMALUNTUNG I KECAMATAN TARERAN KABUPATEN MINAHASA SELATAN - Yosmin Wakur; Maria Y.M.A. Sumakud; Euis F.S. Pangemanan; Wawan Nurmawan (COCOS, 2014)
ABSTRACTThe use of traditional medical plants has been long time by our ancestors and waspassed from generation to generation. This research was on uses of medicinal plants fortraditional medicine in South Minahasa Tontemboan tribe. The data were collected throughinterview using question. The repondensts was traditional healers (Batra). Based on theresults recorded 26 medical plant species from 18 families consisting of 11 types ofherbaceous shrubs 10 species, 5 species trees was used to cure various diseases.Keywords : Traditional, medicine, plants, species, herbaceous shrubs, trees